2012
DOI: 10.1148/radiol.11110175
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Ovarian Cancer: Multiparametric MR Imaging Demonstrates Response- and Metastasis-specific Effects

Abstract: The significant differences in baseline ADCs among primary ovarian cancer, omental cake, and peritoneal deposits indicate that diffusivity profiles may be tumor-site dependent, suggesting biologic heterogeneity of disease. ADC and v(e) parameters correlated with the cytotoxic effects of platinum-based therapy and may be useful response markers, while choline concentration predicted but did not reflect response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 37 publications
(40 reference statements)
3
64
0
1
Order By: Relevance
“…There is a fairly small number of published studies applying conventional FFT-based in vivo MRS to the ovary [47][48][49][50][51][52][53][54][55][56][57][58][59][60]. In Ref.…”
Section: In Vivo Encoded Mrs Time Signals Using Conventional Fourier-mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a fairly small number of published studies applying conventional FFT-based in vivo MRS to the ovary [47][48][49][50][51][52][53][54][55][56][57][58][59][60]. In Ref.…”
Section: In Vivo Encoded Mrs Time Signals Using Conventional Fourier-mentioning
confidence: 99%
“…For all these in vivo studies, the 1 H MRS time signals were processed by the FFT, with fitting-based post-processing in Refs. [49,55,56,58,59].…”
Section: In Vivo Encoded Mrs Time Signals Using Conventional Fourier-mentioning
confidence: 99%
“…With the addition of diffusion-weighted imaging (DWI) further improvement in specificity can be gained, although a substantial number of false positive findings still occur [38,39]. There is also some evidence that DWI may be helpful in reflecting response of advanced stage ovarian cancer to neoadjuvant chemotherapy [40].…”
Section: Possible Added Value Of Magnetic Resonance Imagingmentioning
confidence: 99%
“…Several investigative teams have applied in vivo MRS with the aim of improving ovarian cancer diagnostics. We performed a systematic search 3 of the literature and found published results for 134 malignant ovarian lesions, 114 benign ovarian lesions and 3 lesions of the ovary that were classified as "borderline" (BL), using in vivo proton MRS time signals encoded via clinical (1.5 or 3 T) magnetic resonance (MR) scanners [40,[43][44][45][46][47][48][49][50][51][52][53][54][55]. Appendix 1 provides a summary of the clinical aspects and design of these studies, with salient information concerning the reported MRS data.…”
Section: In Vivo Magnetic Resonance Spectroscopy Of the Ovary: The Prmentioning
confidence: 99%
See 1 more Smart Citation